Perceived stepfamily challenges: a cross-sectional descriptive study among stepfamilies and social and health care professionals - Pakarinen, Anni K.; Selänne, Laura I. M. (University of Victoria Libraries, 2026)
Professionals working in family services often come into contact with stepfamilies. Issues that often need professional support and stepfamily intervention include divorce, custody disputes, children's stress and adjustment problems, and challenges new stepfamilies encounter. The aim of this crosssectional descriptive study was to explore the challenges of stepfamilies as perceived by the families themselves and by the professionals working in services for children, adolescents, and families. Data were collected in the spring of 2018 using semi-structured questionnaires among social and health care professionals and stepfamilies. The data were analyzed using inductive thematic analysis. The challenges reported related mainly to the complexities of managing a stepfamily, including parenting, role conflicts, issues arising from the former life, children's adaptation difficulties, and stepcouple relationships. Five themes were identified from the responses of professionals and parents in stepfamilies: many overlapping stories, children living amid changes, parenting under cross-pressure, love relationship is hard to maintain, and rocky road to a balanced family. These results provide perspectives from a wide range of stakeholders regarding the challenges stepfamilies face. Our study may offer valuable information for professionals working with stepfamilies and for researchers and decision-makers planning interventions for stepfamilies.